THE INFLUENCE OF ONLINE BRAND COMMUNITY, PRODUCT QUALITY, AND PRICE ON BRAND LOYALTY - Faqih, Muhamad; Luhita, Tiladela (Lembaga Penelitian dan Pengabdian kepada Masyarkat-Universitas Terbuka, 2020)
The purpose of this study is to examine the influence of online brand community, product quality, and price on brand loyalty study. To this end, questionnaires were distributed to 96 respondents selected purposively based on three criteria: aged at least 17 years old, having used Xiaomi smartphones for at least one year, and registered as members of Mi Community for at least one year. Data analysis was performed using multiple regression analysis. The results show that the online brand community, product quality, and the price had a positive influence on brand loyalty both partially and simultaneously.